CHINA’S NEW ENERGY STRATEGY IN CENTRAL ASIA IN THE NEW CENTURY - Н. Шaрипкaзы Н.; А. Қaлиоллa (Journal of Oriental Studies, 2019)
The article deals with the energy strategy of China in relation to the States included in the geopoliti cal territory of Central Asia. To date, we are talking about the dynamically developing interests of China in this region, and the main directions of China’s energy strategy are determined. Also, the main strate gic directions and principles of trade and energy contracts and other trade and economic relations of 5 countries of Central Asia with China, including Kazakhstan, Uzbekistan, Turkmenistan, owning the main rich energy sources, will be determined. The article describes the economic advantages and diplomatic approaches to the establishment of relations between Kazakhstan and China, and is widely covered in terms of its effective use. Key words: strategy, Central Asia, politics, energy, China, investment, Soviet Union, reform, oil, gas.